ANALYSIS THE MEANING OF MOTIVATION MESSAGES IN ALBUM “A HEAD FULL OF DREAMS” BY COLDPLAY (Karya Ilmiah Mahasiswa (KIMA), 2024)
The aims other research are to identify massage of motivation to be conveyed through the lyrics of the song and to find out the motivational messages brought of the song .The writer method used was a qualitative research method with a qualitative descriptive approach, While the analysis technique used is the semiotic analysis technique Ferdinand de Saussure, Ferdinand de Saussure's semiotic theory focuses on signifier and signified  Each song lyrics uses illustrations so that it can be analyzed with the semiotic theory of Ferdinand de Saussure.